2017
DOI: 10.1186/s40560-017-0248-6
|View full text |Cite
|
Sign up to set email alerts
|

Transition from intravenous to enteral ketamine for treatment of nonconvulsive status epilepticus

Abstract: BackgroundNonconvulsive status epilepticus (NCSE) is a diagnosis that is often challenging and one that may progress to refractory NCSE. Ketamine is a noncompetitive N-methyl-d-aspartate antagonist that increasingly has been used to treat refractory status epilepticus. Current Neurocritical Care Society guidelines recommend intravenous (IV) ketamine infusion as an alternative treatment for refractory status epilepticus in adults. On the other hand, enteral ketamine use in NCSE has been reported in only 6 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The literature on ketamine treatment for RSE in adults includes eight case reports, seven retrospective case series and a single systematic review (Table 1) 15,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] . Of these 16 studies, nine (56%) report complete seizure control in all patients treated with ketamine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on ketamine treatment for RSE in adults includes eight case reports, seven retrospective case series and a single systematic review (Table 1) 15,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] . Of these 16 studies, nine (56%) report complete seizure control in all patients treated with ketamine.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, ketamine was given within six hours of seizure onset and quickly resulted in complete suppression of seizure activity on EEG 45 . A 2017 case report also describes using ketamine within the first 24 hours of RSE with a similarly prompt treatment response 53 . In both of our cases, ketamine infusion was not introduced for several weeks (after trials of multiple AEDs), but after initiation, achieved burst suppression on EEG within 12 hours.…”
Section: Timing Of Ketamine Administrationmentioning
confidence: 99%
“…It is used either solely or in combination with opioids for the management of acute post-operative and chronic refractory pain (Laskowski et al, 2011 ). Its use in the management of status epilepticus, bipolar disorder, suicidal behavior, major depressive disorder and treatment resistant depression has been demonstrated (Yeh et al, 2011 ; Synowiec et al, 2013 ; Pizzi et al, 2017 ; Borsato et al, 2020 ). Ketamine acts as a non-competitive antagonist of the N-Methyl-D-aspartic acid receptor blocking its action, thereby preventing the development and chronification of pain (Noppers et al, 2010 ).…”
Section: Population Disparity In the Use Of Cyp2b6 Substrates And Consequent Exposure To Substrate-specific Adverse Drug Reaction (Adr)mentioning
confidence: 99%
“…Intravenous administration of ketamine is the conventional method, but enteral administration can also be effective. Pizzi et al [14] reported a patient with nonconvulsive status epilepticus (NCSE) in whom oral ketamine treatment was continued for 6 months, suggesting that enteral ketamine may be a potential adjunct to intravenous ketamine for the treatment of NCSE. Enteral ketamine can reduce the recurrence of SE, the duration of ICU stays, and intubation-related complications.…”
Section: Ketamine In Refractory Status Epilepticusmentioning
confidence: 99%